Korelasi Total Nasal Symptom Score (TNSS) dengan kualitas tidur penderita rhinitis alergi mahasiswa fakultas kedokteran Universitas Mataram - Ni Made Metrya Savita Gera; Didit Yudanto; Muhammad Ghalvan Sahidu; Ilsa Hunaifi (Intisari Sains Medis, 2021)
Introduction. Allergic rhinitis is a disease that is a worldwide concern because of its increasing prevalence and morbidity. Among the various symptoms of RA, nasal congestion is one of the most disturbing symptoms and is often associated with sleep problems. Sleep problems that occur will reduce the quality of sleep and then can cause other health problems. This study aims to determine the relationship between RA symptoms and the sleep quality of RA patients in students of the Faculty of Medicine, University of Mataram.Methods. This cross-sectional study involved students of the Faculty of Medicine, University of Mataram who met the inclusion criteria and did not meet the exclusion criteria. Data were collected by filling out the Total Nasal Symptom Score (TNSS) questionnaire to assess RA symptoms and the Pittsburgh Sleep Quality Index (PSQI) questionnaire to assess sleep quality using the google form application.Results. There were 50 respondents who filled out the questionnaire. Based on the results of the PSQI questionnaire, 98% had poor sleep quality and only 2% had good sleep quality. 46% of respondents with poor sleep quality had moderate RA, and 24% had severe RA. The Spearman rank correlation test showed a significant correlation (p value <0.05) between TNSS RA on sleep quality with a correlation coefficient (r) of 0.558.Conclusion. This shows that there is a moderate positive correlation between the TNSS and the sleep quality of students at the Faculty of Medicine, University of Mataram. Pendahuluan. Rhinitis alergi merupakan penyakit yang kini menjadi perhatian di dunia karena prevalensi dan morbiditasnya yang semakin meningkat. Dari berbagai gejala RA, kongesti hidung merupakan salah satu gejala yang sangat mengganggu dan sering dihubungkan dengan masalah tidur. Masalah tidur yang terjadi akan menurunkan kualitas tidur dan kemudian dapat menyebabkan masalah kesehatan lainnya. Penelitian ini bertujuan untuk mengetahui hubungan gejala RA dengan kualitas tidur penderita RA di mahasiswa Fakultas Kedokteran Universitas Mataram.Metode. Penelitian cross-sectional ini melibatkan mahasiswa Fakultas Kedokteran Universitas Mataram yang memenuhi kriteria inklusi dan tidak memenuhi kriteria eksklusi. Pengambilan data dilakukan melalui pengisian kuesioner Total Nasal Symptom Score (TNSS) untuk menilai gejala RA dan  kuesioner Pittsburgh Sleep Quality Index (PSQI) untuk menilai kualitas tidur menggunakan aplikasi google form.Hasil. Terdapat 50 responden yang melakukan pengisian kuesioner. Berdasarkan hasil kuesioner PSQI, sebanyak 98% memiliki kualitas tidur buruk dan hanya 2% yang memiliki kualitas tidur baik. Sebesar 46% responden dengan kualitas tidur yang buruk memiliki RA derajat sedang, dan 24% memiliki RA derajat berat. Uji korelasi rank Spearman menunjukkan adanya korelasi yang signifikan (nilai p <0,05) antara TNSS RA terhadap kualitas tidur dengan koefisien korelasi (r) sebesar 0,558.Kesimpulan. Hal ini menunjukkan adanya korelasi positif yang cukup antara TNSS dengan kualitas tidur mahasiswa Fakultas Kedokteran Universitas Mataram.